FAKTOR-FAKTOR MENINGKATNYA PERCERAIAN DI KOTA MEDAN DAN KAITANNYA DENGAN PANDEMI COVID-19 - Hamsah Hudafi (Al-Maslahah : Jurnal Ilmu Syariah, 2021)
This paper explains the increase in divorce in the city of Medan and its relation to the Covid-19 pandemic. Divorce during the pandemic has occurred in every region, because many factors support the occurrence of divorce during the Covid-19 pandemic. This encourages the author to conduct research on the divorce rate in the city of Medan. How is divorce in the city of Medan and the factors that cause divorce in Medan and is it related to the Covid-19 pandemic. In conducting research, the method used by the writer is descriptive qualitative and the data sources to be used are written sources from books, journal articles and others. The research location is in the city of Medan especially the Medan religious court class 1A. Based on this research, divorce in the city of Medan continues to increase every year, in 2017 there were 2,057, in 2018 there were 2,509, in 2019 there were 2,757. During the Covid-19 pandemic, divorce cases continued to increase from January to October 2020, there were 2378 divorce cases, the dominant factors in divorce were economic factors, lack of harmony in the family, domestic violence, and irresponsibility. As for the relationship between divorce and the Covi-19 pandemic, there was a period of quarantine during the Covid-19 pandemic as a result, many people were threatened and lost their jobs, this made it difficult to pay for household needs.